Innovation in Icelandic companies : the engagement of Icelandic companies in innovation, their innovation management practices, and the extent of their use of innovation methodologies - Hans Orri Kristjánsson 1980- (2024)
The main objective of this study is to provide an overview of how Icelandic companies engage in innovation, that is, to what extent they actively innovate and how they manage it. Furthermore, the study explores whether companies that report innovation activities allocate resources to support it, and whether they use established innovation methodologies or methods to systematically manage their engagement in it. The study was conducted using a mixed method approach, that is using both quantitative and qualitative data collection. The data was obtained through an online survey and through semi-structured interviews. The findings show that a relatively high percentage of companies in Iceland engage in innovation, both product innovation but also in business process innovation, as well as in other innovation activities. The findings revealed that Icelandic companies don’t necessarily show the integration of innovation into their official business strategies but innovation is often perceived as an integral part their operation. The findings also showed that support from management for innovation was often strong and included willingness to take risk by undertaking innovation projects. Furthermore, the findings showed that the allocation of resources is not a large hindrance to innovation within these companies. When it comes to the use of innovation methodologies, the findings show that Icelandic companies show limited systematic use of innovation methodologies.